First, Do No Harm: Why Philanthropy Needs to Re-Examine Its Role in Reproductive Equity and Racial Justice (Mary Ann Liebert, 2020)
The philanthropic-industrial complex fosters the belief that the most marginalized communities lack an existing repository of historical and contemporary knowledge to address social and health inequities. In so doing, philanthropy has contributed to the diminishing political power, legitimacy, and effectiveness of community voices and leadership in reproductive equity through research injustice, cultural arrogance, philanthropic redlining, and community harm. Black Feminism and Reproductive Justice, as mutually aligned theories and praxes, are described as new ethical standards for philanthropic accountability. Funders must embody the equity they aspire to see and build through the operationalization of cultural rigor to advance structural equity and racial justice and to sustain community engagement in research.